DIFICULDADES DE APRENDIZAGEM DA LINGUA INGLESA NO ENSINO FUNDAMENTAL: UM ESTUDO DE CAMPO - Francisco das Chagas, Antonio; Alves Pereira Neta, Cecilia; Rodrigues do Nascimento Sousa, Francilene; Cassiano de Oliveira Neto, João; de Carvalho Costa, Ricardo (Revista Form@re - Parfor/UFPI, 2026)
.